Description of Stress and Cognitive Function in Patients Non-Hemorrhagic Stroke at Tugurejo Hospital in 2022 - Fathinah Hanin; Siti Istiqomah Khamsiyati; Romadhoni Romadhoni (Jurnal Indonesia Sosial Sains, 2024)
Stroke is the main cause of death in Indonesia, the incidence has increased from 7% to 10%, of which 74% have ischemic strokes. Stress is common in stroke patients. According to research conducted, 58.8% of stroke survivors experienced severe stress, and 60% of stroke survivors experienced decreased or decreased cognitive function after stroke. The research objective was to describe stress and cognitive function in order to reduce stress levels and cognitive function in non-hemorrhagic patients at Tugurejo Hospital in 2022. This type of research is a quantitative descriptive analysis with a cross sectional design. The study population consisted of post-stroke patients who were diagnosed in 2022 by doctors at Tugurejo General Hospital and met the inclusion criteria, namely the Mini Mental State Exam Test Questionnaire (MMSE) and Depression Anxiety Stress Scales (DASS-21) as research instruments, then the data were analyzed using univariate analysis.  The total sample consisted of 40 respondents who were analyzed by univariate. The results of the study describing stress levels in non-hemorrhagic stroke patients at Tugurejo Hospital in 2022 showed that 35% had normal stress levels and 65% had abnormal stress levels. while the picture of cognitive function in non-hemorrhagic stroke patients showed normal results in 32% and impaired cognitive function in 67.5%. Description of stress and cognitive function in non-hemorrhagic stroke patients at Tuguurejo General Hospital in 2022. Based on risk factors, gender, age, education, occupation, pre-existing conditions and stroke onset, the results showed abnormal levels of stress and disruption of cognitive function.